Membrane material for alkaline system and application
By introducing alkali-resistant hydrophilic macromolecules into alkali-resistant and stable inorganic materials and blending them with organic polymers, high ion conductivity and low cost membrane materials are prepared, which solves the problems of low ion conductivity and high cost of existing membrane materials in alkaline systems, and significantly improves the performance of energy storage and hydrogen energy devices.
Patent Information
- Application Number
- CN202311265265.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The membrane materials used in existing alkaline systems have shortcomings in terms of ion conductivity and cost, especially the perfluorosulfonic acid ion film has low ion conductivity, while the Zirfon film has poor gas barrier properties and is expensive.
By introducing the hydrophilic small molecules with double bonds into the alkali-resistant and stable inorganic material, they are polymerized into alkali-resistant and hydrophilic macromolecules in the pores of the inorganic material to form a material containing alkali-resistant and hydrophilic macromolecules in the alkali-resistant and stable inorganic material, and blended with the organic polymer to prepare a composite film.
It improves the ion conductivity and selectivity of the membrane material, reduces the material cost, and is suitable for alkaline liquid flow batteries and alkaline water electrolysis hydrogen production devices.
Smart Images

Figure HDA0004474143600000011
Abstract
Description
Technical Field
[0001] The present invention relates to a membrane material for alkaline system and its preparation and application, and in particular to the application of such membrane in energy conversion and storage devices of alkaline system such as alkaline system liquid flow battery and alkaline water electrolysis for hydrogen production. Background Art
[0002] With the development of society, human demand for energy is gradually increasing, but non-renewable energy such as fossil energy is gradually depleting, while renewable energy such as wind energy, solar energy, tidal energy, etc., have received widespread attention due to their renewability and environmental friendliness. However, the discontinuity, instability, and unpredictability of renewable energy generation have seriously hindered its widespread application, and energy storage technology is an important support for achieving safe and stable power supply of renewable energy. There are physical and chemical energy storage in energy storage technology, among which chemical energy storage is more widely used, and electrochemical energy storage is the most common energy storage device in chemical energy storage. In electrochemical energy storage, liquid flow battery energy storage technology has broad application prospects in the field of large-scale energy storage due to its independent energy density and power density, flexible design, safety and reliability, environmental friendliness, and small geographical restrictions. Alkaline system liquid flow batteries such as alkaline zinc-iron liquid flow batteries and alkaline organic / iron liquid flow batteries have received widespread attention in the field of energy storage due to their abundant resources, low prices, and high kinetics, and have good development prospects.
[0003] In addition to energy storage technology, hydrogen energy can help achieve large-scale and efficient consumption of renewable energy and redistribute energy between different industries and regions. It can act as an energy buffer to improve the resilience of the energy system, which is not only conducive to reducing carbon emissions in the transportation process, but also has a more extensive application in reducing carbon emissions in the industrial energy sector, such as replacing coke in the metallurgical industry and reducing carbon emissions in building heating. Therefore, hydrogen production based on renewable energy electrolysis has shown a rapid development trend in recent years internationally. Many countries have begun to set development goals for hydrogen energy in industries such as industry, construction, and electricity outside the transportation field, and have made positive progress in government planning and application demonstration. Among the many water electrolysis hydrogen production technologies, alkaline water electrolysis hydrogen production technology (ALK) has the advantages of low cost, long life, and large scale (single cell can reach 7.5MW); in addition, alkaline electrolyzer technology is the most mature and has the lowest production cost.
[0004] As a key core material for energy storage and hydrogen energy, the main function of membrane materials is to separate the positive and negative active materials / gases from each other and transfer carriers to form the internal circuit of the battery. The membrane materials are required to have high ion selectivity, high ion conductivity, high stability, low cost, etc. Perfluorosulfonic acid ion membrane (Nafion series membrane) is a type of membrane material widely used in liquid flow batteries. This type of membrane material has low ion conductivity in alkaline systems, which is not conducive to improving battery performance; Zirfon is the most commonly used membrane material for alkaline water electrolysis to produce hydrogen. It has the advantage of high ion conductivity, but its gas barrier is poor and its price is high, which is not conducive to reducing the material cost of alkaline water electrolysis hydrogen production equipment.
[0005] Therefore, designing and developing high-performance, low-cost membrane materials is of great significance to improving the performance of energy storage and hydrogen energy devices, reducing material costs, and promoting their large-scale application.
[0006] In view of the problems of low ion conductivity of perfluorosulfonic acid ion membrane in alkaline solution, poor gas barrier of Zirfon membrane and high price, the present application designs and prepares a membrane material for alkaline system, which introduces hydrophilic small molecules with double bonds into the interior of inorganic materials with alkali resistance and stability, and polymerizes hydrophilic small molecules with double bonds into alkali-resistant hydrophilic macromolecules in the pores of inorganic materials, thereby obtaining a material (represented by material A) in which alkali-resistant hydrophilic macromolecules are encapsulated in inorganic materials with alkali resistance and stability. Alkali-resistant hydrophilic macromolecules form a continuous hydrogen bond network structure in the pores of inorganic materials, reduce the entrance activation energy of ions at the pores, increase the diffusion rate of ions in the pores, and improve the ion conductivity of the material. The composite membrane prepared by blending and compounding material A with organic polymers has both high ion conductivity and high ion selectivity, and has good performance in alkaline flow battery systems and alkaline water electrolysis hydrogen production devices. Summary of the invention
[0007] To achieve the above effects, the specific technical solutions are as follows:
[0008] The membrane material for alkaline system is prepared by compounding and blending an alkali-resistant and stable inorganic material encapsulating an alkali-resistant and hydrophilic macromolecular material with an organic polymer.
[0009] The organic polymer is one or more of a cation exchange resin with a rigid segment structure (such as one or more of sulfonated polysulfone, sulfonated polyimide, sulfonated polyether ketone, and sulfonated polybenzimidazole), a polymer resin with a rigid segment structure (such as one or more of polysulfone, polyether sulfone, and polyether ketone), a polymer resin with a nitrogen heterocyclic structure (such as one or more of chloromethylated polysulfone grafted with one or more of polybenzimidazole, pyridine, or imidazole), a perfluorosulfonic acid resin, a polyolefin, and the like.
[0010] The alkali-resistant and stable inorganic materials are ZIF-8, LDH, and ZrO2, wherein ZIF-8 and LDH can control their morphology, interlayer spacing and other properties by regulating the preparation process and conditions (such as precursor ion ratio, synthesis temperature, hydrothermal time, etc.); the hydrophilic macromolecules are sodium polystyrene sulfonate, polyvinyl pyridine, polyvinyl imidazole, and polyvinyl pyrrolidone.
[0011] The material in which alkali-resistant and hydrophilic macromolecules are encapsulated in the alkali-resistant and stable inorganic material is prepared by the following method: placing the alkali-resistant and stable ZIF-8, LDH, and ZrO2 inorganic materials in a solution of sodium styrene sulfonate, vinyl pyridine, vinyl imidazole, and N-vinyl pyrrolidone, wherein the mass fraction of sodium styrene sulfonate, vinyl pyridine, vinyl imidazole, and N-vinyl pyrrolidone in the solution is 0.1wt% to 20wt%, preferably 1wt% to 10wt%; allowing the above-mentioned small molecules to enter the pores or layers of the alkali-resistant and stable ZIF-8, LDH, and ZrO2 inorganic materials, and through addition polymerization, allowing the above-mentioned small molecules to generate alkali-resistant and hydrophilic macromolecules (large in size, fixed in the pores or layers of the inorganic material) in the pores or layers of the inorganic material, thereby obtaining a material in which alkali-resistant and hydrophilic macromolecules are encapsulated in the alkali-resistant and stable inorganic material, i.e., material A.
[0012] Material A is compounded onto the surface of the ion membrane or porous membrane prepared from the above polymer by spraying, spin coating, blade coating, sol adhesion and the like, and the thickness of the composite layer formed by material A on the membrane surface is 1 to 20 μm; or material A is blended with the above polymer by a solvent volatilization method or a phase inversion method to prepare a blended membrane, and the mass of material A accounts for 5wt% to 85wt% of the mass of the polymer, preferably 15wt% to 45wt%.
[0013] The membrane material is used in energy conversion and storage devices in alkaline systems.
[0014] The energy conversion and storage devices of the alkaline system include, but are not limited to, flow batteries and hydrogen production by water electrolysis.
[0015] The present invention introduces hydrophilic small molecules with double bonds into the interior of an inorganic material with alkali resistance and stability, and the hydrophilic small molecules with double bonds polymerize into alkali-resistant hydrophilic macromolecules in the pores of the inorganic material, thereby obtaining a material (represented by material A) in which alkali-resistant hydrophilic macromolecules are encapsulated in an inorganic material with alkali resistance and stability. The alkali-resistant hydrophilic macromolecules form a continuous hydrogen bond network structure in the pores of the inorganic material, reduce the entrance activation energy of ions at the pores, increase the diffusion rate of ions in the pores, and improve the ion conductivity of the material. The composite membrane prepared by blending and compounding material A with an organic polymer has both high ion conductivity and high ion selectivity, and has good performance in an alkaline liquid flow battery system and an alkaline water electrolysis hydrogen production device.
[0016] Beneficial results of the present invention:
[0017] 1. By introducing alkali-resistant hydrophilic macromolecules into the pores or layers of inorganic materials with alkali resistance and stability during polymerization, a continuous hydrogen bond network structure is formed in the pores of the inorganic materials, the entrance activation energy of the carriers at the pore mouth is reduced, the diffusion rate of ions in the pores is increased, and the ion conductivity of the material is improved.
[0018] 2. The alkali-resistant and hydrophilic macromolecular material encapsulated in the alkali-resistant and stable inorganic material is compounded onto the polymer ion membrane or porous membrane by spraying, spin coating, blade coating, sol adhesion, blending and other methods, thereby improving the selectivity (ion selectivity, gas barrier properties) of the membrane material while ensuring the high ion conductivity of the membrane material.
[0019] 3. The membrane material proposed in the present invention has excellent alkali resistance and stability, which expands the selection range of membrane materials for energy conversion and storage devices in alkaline systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of a material with alkaline-resistant and hydrophilic macromolecules encapsulated in LDH DETAILED DESCRIPTION
[0021] Comparative Example 1
[0022] Polyethersulfone (PES) and sulfonated polyetheretherketone (SPEEK) were blended (the solid content of the polymer (PES and SPEEK, the same below) was 30wt%, PES:SPEEK=9:1 (mass ratio, the same below), and DMAc was used as the solvent). Under the conditions of room temperature and 30% humidity, water was used as a non-solvent bath, and a PES / SPEEK porous ion conductive membrane with a thickness of 80μm was prepared by immersion phase inversion method. The PES / SPEEK porous ion conductive membrane was used as a matrix, and a dispersion composed of original magnesium aluminum hydrotalcite (LDH) was uniformly sprayed on both sides of the matrix (using 1.0wt% Nafion solution as the dispersion, and the mass ratio of LDH / Nafion was 8 / 2) and then placed at room temperature for 2min, forming LDH separation layers with a thickness of 15μm on both sides, and an alkaline zinc-iron liquid flow battery was assembled using it. The positive electrode electrolyte composition was: 0.8mol L -1 Fe(CN)6 4- +3mol L -1 KOH aqueous solution; negative electrode electrolyte composition: 0.4 mol L -1 Zn(OH)4 2- +3mol L - 1 NaOH aqueous solution; the volume of positive and negative electrolytes is 80mL each; both positive and negative electrodes are porous carbon felt electrodes, and graphite plates are used as current collectors. Electrode effective area: 48cm 2The battery adopts constant current charge and discharge mode, at 80mA cm -2 The current density was 80 mA cm-1 for 18 min and then the voltage was cut off. -2 The battery was discharged to 0.1 V under the condition of current density of . The coulombic efficiency of the battery was 98.77% and the voltage efficiency was 86.62%.
[0023] Example 1
[0024] The above 0.1g magnesium aluminum hydrotalcite (LDH) was placed in 200mL of an aqueous solution containing 5wt% sodium styrene sulfonate by mass (containing 0.4g potassium persulfate free radical initiator), and after mechanical stirring at room temperature for 2h, vacuum was applied under a negative pressure of 1MPa (during the vacuum process, the LDH pores were in a negative pressure state, and the styrene sulfonate ions in the solution and the potassium persulfate free radical initiator entered the interlayer), allowing the sodium styrene sulfonate and free radical initiator in the solution to fully enter the LDH interlayer. Then, under the protection of a nitrogen atmosphere, the mixture was polymerized at 70°C and normal pressure for 2h, and the solution after the polymerization reaction was filtered and washed with water to obtain an LDH powder (containing 3wt% sodium polystyrene sulfonate (degree of polymerization of 7 to 11) in the interlayer. Figure 1 , the content of sodium polystyrene sulfonate between LDH powder layers was obtained by thermogravimetric analysis).
[0025] Polyethersulfone (PES) and sulfonated polyetheretherketone (SPEEK) were blended (the solid content of the polymer (PES and SPEEK, the same below) was 30wt%, PES:SPEEK=9:1 (mass ratio, the same below), and DMAc was used as the solvent). Under the conditions of room temperature and 30% humidity, water was used as a non-solvent bath, and a PES / SPEEK porous ion conductive membrane with a thickness of 80μm was prepared by immersion phase inversion method. The PES / SPEEK porous ion conductive membrane was used as a matrix, and a dispersion consisting of LDH powder containing sodium polystyrene sulfonate between layers (using 1.0wt% Nafion solution as the dispersion, and the mass ratio of LDH containing sodium polystyrene sulfonate between layers / Nafion was 8 / 2) was uniformly sprayed on both sides of the matrix and placed at room temperature for 2 minutes, forming a 15μm thick LDH separation layer containing sodium polystyrene sulfonate between layers on both sides, and an alkaline zinc-iron liquid flow battery was assembled using it, and the positive electrode electrolyte composition was: 0.8mol L -1 Fe(CN)6 4- +3mol L -1 KOH aqueous solution; negative electrode electrolyte composition: 0.4 mol L -1 Zn(OH)4 2- +3mol L -1 NaOH aqueous solution; the volume of positive and negative electrolytes is 80mL each; both positive and negative electrodes are porous carbon felt electrodes, and graphite plates are used as current collectors. Electrode effective area: 48cm 2The battery adopts constant current charge and discharge mode, at 80mA cm -2 The current density was 80 mA cm-1 for 18 min and then the voltage was cut off. -2 The battery was discharged to 0.1V under the condition of current density of . The coulombic efficiency of the battery was 99.12%. Since sodium polystyrene sulfonate formed a continuous hydrogen bond network structure in LDH, it reduced the entrance activation energy of carriers at the pore mouth, increased the diffusion rate of ions in the pores, and improved the ion conductivity of the material. Therefore, the battery voltage efficiency could reach 91.33%.
[0026] Comparative Example 2
[0027] The original magnesium aluminum hydrotalcite (LDH) dispersion (isopropanol as solvent, mass fraction of 1wt%) was evenly sprayed onto the designated area of the glass plate, and then the glass plate was heated on a hot plate at 50°C for 1 hour to remove the solvent in the dispersion. Subsequently, a 200μm thick scraper was used to evenly scrape the polyethersulfone (PES) and sulfonated polyetheretherketone (SPEEK) blend (polymer (PES and SPEEK, the same below) solid content of 30wt%, PES:SPEEK=9:1 (mass ratio, the same below), DMAc as solvent) casting liquid on the sprayed area of the glass plate at room temperature and 20% humidity. Finally, the glass plate was immersed in water for 30 minutes to form a composite membrane with a thickness of ~5μm LDH composite. It was used to assemble an alkaline zinc-iron liquid flow battery, and the positive electrode electrolyte composition was: 0.8mol L - 1 Fe(CN)6 4- +3mol L -1 KOH aqueous solution; negative electrode electrolyte composition: 0.4 mol L -1 Zn(OH)4 2- +3mol L -1 NaOH aqueous solution; the volume of positive and negative electrolytes is 80mL each; both positive and negative electrodes are porous carbon felt electrodes, and graphite plates are used as current collectors. Electrode effective area: 48cm 2 The battery adopts constant current charge and discharge mode, at 80mA cm -2 The current density was 80 mA cm-1 for 18 min and then the voltage was cut off. -2 The battery was discharged to 0.1 V under the condition of current density of . The coulombic efficiency of the battery was 97.93% and the voltage efficiency was 87.13%.
[0028] Example 2
[0029] The above 0.1g magnesium aluminum hydrotalcite (LDH) was placed in 200mL of an aqueous solution containing 5wt% sodium styrene sulfonate by mass (containing 0.4g potassium persulfate free radical initiator), stirred for 3h, and then vacuumed under a negative pressure of 1MPa (during the vacuum process, the LDH pores were in a negative pressure state, and the styrene sulfonate ions in the solution and the potassium persulfate free radical initiator entered the interlayer), allowing the sodium styrene sulfonate and free radical initiator in the solution to fully enter the LDH interlayer. Then, under the protection of a nitrogen atmosphere, polymerized at 70°C and normal pressure for 2h, the solution after the polymerization reaction was filtered and washed with water to obtain LDH powder containing 3wt% sodium polystyrene sulfonate (polymerization degree of 7 to 11) in the interlayer.
[0030] The LDH dispersion containing sodium polystyrene sulfonate between the layers (isopropanol as solvent, mass fraction of 1wt%) was uniformly sprayed onto the designated area of the glass plate, and then the glass plate was heated on a hot plate at 50°C for 1 hour to remove the solvent in the dispersion. Subsequently, a 200μm thick scraper was used to evenly scrape the polyethersulfone (PES) and sulfonated polyetheretherketone (SPEEK) blend (polymer (PES and SPEEK, the same below) solid content of 30wt%, PES:SPEEK=9:1 (mass ratio, the same below), DMAc as solvent) casting liquid on the sprayed area of the glass plate at room temperature and 20% humidity. Finally, the glass plate was immersed in water for 30 minutes to form a composite membrane with a thickness of ~5μm and LDH containing sodium polystyrene sulfonate between the layers. It was used to assemble an alkaline zinc-iron liquid flow battery, and the positive electrode electrolyte composition was: 0.8mol L -1 Fe(CN)6 4- +3mol L -1 KOH aqueous solution; negative electrode electrolyte composition: 0.4 mol L -1 Zn(OH)4 2- +3mol L -1 NaOH aqueous solution; the volume of positive and negative electrolytes is 80mL each; both positive and negative electrodes are porous carbon felt electrodes, and graphite plates are used as current collectors. Electrode effective area: 48cm 2 The battery adopts constant current charge and discharge mode, at 80mA cm -2 The current density was 80 mA cm-1 for 18 min and then the voltage was cut off. -2 The battery was discharged to 0.1 V under the condition of current density of . The coulombic efficiency of the battery was 98.43%, and the voltage efficiency was increased to 91.66%.
[0031] Comparative Example 3
[0032] The original ZIF-8 dispersion (ethanol as solvent, mass fraction of 1wt%) was uniformly sprayed onto the designated area of the glass plate, and then the glass plate was heated on a hot plate at 50°C for 1 hour to remove the solvent in the dispersion. Subsequently, a 200μm thick scraper was used to evenly scrape the polyethersulfone (PES) and sulfonated polyetheretherketone (SPEEK) blend (polymer (PES and SPEEK, the same below) solid content of 30wt%, PES:SPEEK=9:1 (mass ratio, the same below), DMAc as solvent) casting liquid on the spraying area of the glass plate, and finally the glass plate was immersed in water for 30 minutes to form a composite membrane of 10μm ZIF-8 composite. It is used in an alkaline electrolytic cell, with a nickel mesh with a mesh number of 60 and an integrated electrode loaded with a nickel-iron catalyst layer (the nickel-iron catalyst layer has a thickness of 100 nm to 200 nm (here 160 nm), and an atomic ratio of Fe / Ni=10 to 15:100 (here 12:100)) as a HER electrode (the preparation method is shown in Example 2 of patent CN110197909A (Nickel-iron catalytic material, its preparation method and application in electrolysis of water to produce hydrogen and preparation of liquid solar fuel)), and a nickel mesh with a mesh number of 60 as an electrode on the OER side, and the effective area of the electrode is 9 cm 2 , stainless steel plate as current collector, 6 mol L -1 KOH solution. Test conditions: 400mA cm -2 Constant current charging, test temperature 70 ° C. The structure of the electrolytic cell includes a current collector, an integrated electrode loaded with a HER catalyst, a membrane, an alkaline solution, and a current collector arranged in sequence. The electrolysis voltage of the electrolytic cell is 1.92V.
[0033] Example 3
[0034] 0.1g of the above ZIF-8 was placed in 200mL of an aqueous solution containing 5wt% sodium styrene sulfonate (containing 0.5g potassium persulfate free radical initiator), stirred for 4h, and then vacuumed under a negative pressure of 2MPa (during the vacuum process, the ZIF-8 pores were in a negative pressure state, and the styrene sulfonate ions in the solution and the potassium persulfate free radical initiator entered the interlayer), allowing the sodium styrene sulfonate and free radical initiator in the solution to fully enter the ZIF-8 pores. Then, under the protection of a nitrogen atmosphere, polymerized at 70°C and normal pressure for 3h, the solution after the polymerization reaction was filtered and washed with water to obtain ZIF-8 powder containing 4.5wt% sodium polystyrene sulfonate (polymerization degree of 9 to 14) between the layers.
[0035] The ZIF-8 dispersion containing sodium polystyrene sulfonate in the pores (ethanol as solvent, mass fraction of 1wt%) was uniformly sprayed onto the designated area of the glass plate, and then the glass plate was heated on a hot plate at 50°C for 1 hour to remove the solvent in the dispersion. Subsequently, a 200μm thick scraper was used to evenly scrape the polyethersulfone (PES) and sulfonated polyetheretherketone (SPEEK) blend (polymer (PES and SPEEK, the same below) solid content of 30wt%, PES:SPEEK=9:1 (mass ratio, the same below), DMAc as solvent) casting liquid on the spraying area of the glass plate at room temperature and 30% humidity. Finally, the glass plate was immersed in water for 30 minutes to form a composite membrane with a thickness of 10μm and a ZIF-8 composite containing sodium polystyrene sulfonate between layers. It is used in an alkaline electrolytic cell, with a nickel mesh with a mesh number of 60 and an integrated electrode loaded with a nickel-iron catalyst layer (the nickel-iron catalyst layer has a thickness of 100 nm to 200 nm (here 160 nm), and an atomic ratio of Fe / Ni=10 to 15:100 (here 12:100)) as a HER electrode (the preparation method is shown in Example 2 of patent CN110197909A (Nickel-iron catalytic material, its preparation method and application in electrolysis of water to produce hydrogen and preparation of liquid solar fuel)), and a nickel mesh with a mesh number of 60 as an electrode on the OER side, and the effective area of the electrode is 9 cm 2 , stainless steel plate as current collector, 6 mol L -1 KOH solution. Test conditions: 400mA cm -2 Constant current charging, test temperature 70℃. The structure of the electrolytic cell includes a current collector, an integrated electrode loaded with a HER catalyst, a membrane, an alkaline solution, and a current collector arranged in sequence. The electrolysis voltage of the electrolytic cell is reduced to 1.71V, which greatly reduces the voltage in the process of hydrogen production by alkaline water electrolysis, which is of great significance for reducing the energy consumption in the process of hydrogen production by alkaline water electrolysis.
Claims
1. A membrane material for an alkaline system, characterized in that: The membrane material is a composite membrane prepared by attaching an alkali-resistant and stable inorganic material encapsulating an alkali-resistant and hydrophilic macromolecular material to the surface of an organic polymer membrane, or a blended membrane prepared by blending an alkali-resistant and stable inorganic material encapsulating an alkali-resistant and hydrophilic macromolecular material with an organic polymer.
2. The membrane material for alkaline system according to claim 1, characterized in that: The organic polymer is one or more of a cation exchange resin with a rigid segment structure (such as one or more of sulfonated polysulfone, sulfonated polyimide, sulfonated polyether ketone, and sulfonated polybenzimidazole), a polymer resin with a rigid segment structure (such as one or more of polysulfone, polyether sulfone, and polyether ketone), a polymer resin with a nitrogen heterocyclic structure (such as one or more of chloromethylated polysulfone grafted with one or more of polybenzimidazole, pyridine, or imidazole), a perfluorosulfonic acid resin, a polyolefin, and the like.
3. The membrane material for alkaline system according to claim 1, characterized in that: The alkali-resistant and stable inorganic material is one or more of ZIF-8, layered double hydroxide (LDH, with an interlayer spacing of 0.6 to 1.2 nm), and zirconium dioxide (ZrO2, with a pore size of 2 to 8 nm); the hydrophilic macromolecule is one or more of sodium polystyrene sulfonate, polyvinyl pyridine, polyvinyl imidazole, and polyvinyl pyrrolidone.
4. The membrane material for alkaline system according to claim 1, characterized in that: The alkali-resistant and stable inorganic material with an alkali-resistant and hydrophilic macromolecular material encapsulated therein is prepared by the following method: placing one or more of the alkali-resistant and stable ZIF-8, LDH, and ZrO2 inorganic materials in a solution of one or more of sodium styrene sulfonate, vinyl pyridine, vinyl imidazole, and N-vinyl pyrrolidone, wherein the mass fraction of one or more of the sodium styrene sulfonate, vinyl pyridine, vinyl imidazole, and N-vinyl pyrrolidone in the solution is 0.1wt% to 20wt%, preferably 1wt% to 10wt%; allowing the above-mentioned small molecules to pass through adsorption or layer The small molecules enter the pores or layers of one or more alkali-resistant and stable ZIF-8, LDH, and ZrO2 inorganic materials by means of inter-exchange, and through addition polymerization or polymerization reaction, the above-mentioned small molecules are generated into alkali-resistant and hydrophilic macromolecules (large in size, fixed in the pores or layers of the inorganic materials) in the pores or layers of the inorganic materials, thereby obtaining a material in which alkali-resistant and hydrophilic macromolecules are encapsulated in the alkali-resistant and stable inorganic material, i.e., material A, wherein the degree of polymerization of the macromolecules in the pores or layers is 2 to 20, preferably 5 to 15, and the mass content of the hydrophilic macromolecules in material A is 0.02wt%-7wt%, preferably 1wt% to 6wt%.
5. The membrane material for alkaline system according to claim 1, characterized in that: The alkali-resistant and stable inorganic material encapsulating the alkali-resistant and hydrophilic macromolecular material is attached to the surface of the ion membrane or porous membrane prepared from the organic polymer by one or more methods such as spraying, spin coating, blade coating or sol adhesion, and the thickness of the composite layer formed by the alkali-resistant and stable inorganic material encapsulating the alkali-resistant and hydrophilic macromolecular material on the membrane surface is 1 to 20 μm; Alternatively, an alkali-resistant and stable inorganic material encapsulating an alkali-resistant and hydrophilic macromolecular material is blended with an organic polymer by a blending method and a solvent volatilization method or a phase inversion method is used to prepare a blended membrane, wherein the mass of the alkali-resistant and stable inorganic material encapsulating an alkali-resistant and hydrophilic macromolecular material accounts for 5wt% to 85wt% of the polymer mass, preferably 15wt% to 45wt%.
6. Use of the membrane material according to any one of claims 1 to 5 in energy conversion and storage devices in alkaline systems.
7. The use according to claim 6, characterized in that: The energy conversion and storage device of the alkaline system includes but is not limited to a flow battery or a water electrolysis hydrogen production electrolysis cell.
Citation Information
Patent Citations
Ferronickel catalytic material and preparation method thereof, and application of ferronickel catalytic material in preparing hydrogen by electrolyzing water and preparation of liquid solar fuel
CN110197909A
Preparation method of organic-inorganic composite membrane for hydrogen production by alkaline electrolysis of water
CN115142089A
Preparation method and application of super-hydrophilic composite membrane capable of being used for removing various pollutants in water body
CN115999387A
Preparing nano sheet type polymer using LDHs as template and its preparing method
CN1616495A
Diaphragm for alkaline water electrolysis and alkaline water electrolytic cell using the same
JP2015117417A
Cited By
Low-cost proton exchange membrane and preparation method thereof
CN120300235A
Magnetic field regulation and control magnesium-iron double-metal hydroxide ordered alkaline diaphragm and preparation method thereof
CN121628179A